Lumped Parameter and Circuit Models of Electromechanical Switching Device Electromagnet - Bajda, Yevgen I.; Clemens, Markus; Pantelyat, Michael G.; Korol, Olena G. (Technischen Universität Graz, Austria, 2020)
Forced DC electromagnets are widely used in modern electromechanical switching devices. In cases, where the total costs of simulation of high-fidelity electromagnetic field's 3D and even 2D models are unacceptably high, alternative techniques based on lumped parameters and magnetic circuit models of switching device electromagnets can be used. The paper presents a technique for calculating the dynamics of forced DC electromagnets using the Maple code as an example of simulation of the magnetic circuit of an electromagnet used in vacuum contactors.
Keywords: electromagnet; lumped parameters; magnetic circuit; switching device